Shafardeesyabel Stationary & Magazine Shop - Ahmadsah, Nur Shatila; Zullkapli, Farhanah Syaza; Nelson, Nursyafiqah; Saral Mohammad, Nabilah; Damit, Nur Adibah (2013)
The name of our company is Shafardeesyabel Stationary & Magazine Shop. Our main activity of this project is preparing and providing stationary, magazines and newspaper to customer. Although there is many competitors of this nature business, but we are believe that there is an opportunity for us to be one of them. The vision of this business is to meet customer satisfaction, to provide value-for money products and quality services to our customers, a pleasant working environment for people and to be a good corporate citizen. Mission of this company is to serve our people, to grow with our society and to mutually benefit from the world. It means that, whatever or how many of our competitor, we are just want to serve people no matter how hard it is as long as we are serve them to fulfil their needs. Our location is at Sulaman Sentral, Sepanggar. This is located near with the two popular Universities in Sabah which is University Malaysia Sabah and University Technology MARA Sabah. This place is the most strategic place to come and the most affordable price rentals. It is also placed in a between of these two universities, and near with the others housing area Menggatal and Sepanggar such as University Apartment 1 & 2, University Condominium, Kingfisher and so on. Our target market is students, lecturers, and the whole organizations in UiTM, UMS, Politeknik, IKP, people who lives around the area Bukit Sepanggar, Indah Permai, Kg.Lokub, Sri Maju, Kingfisher Sulaman and others. Shafardeesyabel Stationary & Magazine shop will be expected to operate on 1st January 2012. We choose the specific date because we want to discover more about this opportunity.